Prevalence of Streptococcus B in pregnant women with preterm birth and its association with adverse outcomes - Marianna Camilo Rezende; Thamirys Pereira Rodrigues; Andressa Paes Medeiros de Freitas; Karina Souza Lopes; Edward Araujo Júnior; Alberto Borges Peixoto (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: the objective this study was evaluating the prevalence of maternal colonization by Group B beta-hemolytic Streptococcus (GBS) in pregnant women who delivered preterm and its relationship with adverse maternal/perinatal outcomes. Methods: we carried out a retrospective cohort study with singleton pregnancies with or without a culture for GBS (vaginal-rectum) who delivered spontaneously <37 weeks of gestation. Results: the study included 190 pregnant women, 53.1% (101/190) did not undergo culture for GBS and 46.8% (89/101) have done. Among the patients who had a culture, 13.5% (12/89) had positive culture for GBS and 86.5% (77/89) had a negative culture. Pregnant women without GBS culture had higher prevalence of preterm birth (74.3 vs. 59.6%, p=0.031) and lower prevalence of antibiotic prophylaxis (27.7 vs. 56.2%, p<0.001) than pregnant women with GBS culture. Higher prevalence of crystalline penicillin G use was observed in pregnant women with positive culture compared to pregnant women with negative culture for GBS (100 vs. 39%, p<0.0001). There was no significant association between pregnant women with or without a culture for GBS or positive and negative GBS cultures and adverse maternal/perinatal outcomes. Conclusion: No significant association was found between GBS culture or not, GBS positive or negative culture, adequate or inadequate GBS prophylaxis, and the prevalence of adverse maternal/perinatal outcomes.